ChemInform Abstract: Asymmetric [4 + 3] Cycloadditions of Enantiomerically Enriched Epoxy Enolsilanes. Issue 19 (18th April 2013) - Lo, Brian; Lam, Sarah; Wong, Wing‐Tak; Chiu, Pauline
Abstract The title reaction of the enolsilane (I) gives a mixture of endo and exo cycloadducts with unexpected high enantioselectivity.